2009
DOI: 10.1038/hr.2009.66
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of antihypertensive therapy with add-on angiotensin II type 1 receptor blocker after successful coronary stent implantation

Abstract: This study was performed to evaluate the safety and efficacy of additional antihypertensive therapy with angiotensin II type 1 receptor blocker (ARB; olmesartan or valsartan) after successful stent implantation in patients with coronary artery disease (CAD). Fifty patients with CAD after successful stent implantation were included in this study. They were divided into an ARB group, which initially received olmesartan (n¼20, 14±8 mg day À1 ) or valsartan (n¼20, 60±23 mg day À1 ) immediately after stent implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…The present study demonstrated that olmesartan significantly reduced serum hsCRP levels as previously reported. 25,[45][46][47] However, the changes in hsCRP levels were not associated with those in FMD. As in the case of microalbuminuria, as RAS inhibition produces pleiotropic effects, there may not be a simple one-to-one correlation between serum hsCRP levels and endothelial function either.…”
Section: Discussionmentioning
confidence: 91%
“…The present study demonstrated that olmesartan significantly reduced serum hsCRP levels as previously reported. 25,[45][46][47] However, the changes in hsCRP levels were not associated with those in FMD. As in the case of microalbuminuria, as RAS inhibition produces pleiotropic effects, there may not be a simple one-to-one correlation between serum hsCRP levels and endothelial function either.…”
Section: Discussionmentioning
confidence: 91%
“…The beneficial effects of both olmesartan 24 and candesartan 25 on blood pressure were already known. With regard to the effects of candesartan and olmesartan on adipokines, we know that ADN is a protein exclusively synthesized by adipocytes, which decreases in obese patients and is inversely related to glucose and insulin.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in patients with CAD, olmesartan medoxomil and valsartan both produced significant reductions in BP, but only olmesartan medoxomil induced a significant reduction in hsCRP [116]. Losartan has also been shown to reduce hsCRP in newly diagnosed hypertensive patients who are at CV disease risk [117].…”
Section: Hscrpmentioning
confidence: 99%